The Influence of Green Accounting on the Profitability of Food and Beverage Subsector Companies Listed on the Indonesia Stock Exchange for the 2018-2023 Period - Billa, Ghina Salsa; Prima Jaya, Fanlia (Hut Publication Business and Management, 2024)
The aim of this research is to find out whether green accounting has on effect on the profitability of food and beverage sub-sector companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2023 period. Green Accounting is measured by environmental cost and environmental performance. Profitability is measured by financial ratios, namely Return On Assets (ROA) and Return On Equity (ROE).The population in this research is all food and beverage. Subsector companies listed on the IDX. The sample was taken based on a purposive sampling technique and based on predetermined criteria, a sample of 7 companies was obtained with observations of 51 companies. The analytical method used is simple linier regression analysis using SPSS version 25. The research result show that green accounting has a significant effect on company profitability